A memorable experience at Faculty of Pharmacy Universitas Hasanuddin / Dr. Norkasihan Ibrahim and Dr. Gurmeet Kaur Surindar Singh - Ibrahim, Norkasihan; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
We are delighted to share the exciting news of our esteemed faculty member, Dr. Norkasihan Ibrahim's recent participation as a visiting professor at the Faculty of Pharmacy, Universitas Hasanuddin (UNHAS) in Makassar, Indonesia. From September 4th to September 10th, 2023, Dr. Norkasihan, who is also the Faculty of Pharmacy UiTM Deputy Dean of Industry, Community, and Alumni Network (ICAN), had the honour of being part of UNHAS' International Lecture Programme, fostering academic exchange and collaboration. Ms. Andi Anggriani, a faculty member and research partner at UNHAS, and Yusril, a UNHAS alumnus, welcomed Dr.Norkasihan warmly upon his arrival at the Makassar International Airport on Sunday, September 3. Throughout the visit, she resided at the vibrant UNHAS Hotel, located within the bustling campus. During the programme, Dr. Norkasihan delivered seven captivating lectures to students in the Master of Clinical Pharmacy and Bachelor of Pharmacy programmes. The opportunity to engage with the students and witness their active participation was immensely satisfying. A highlight of the lectures was a medication counselling role-playing activity that received enthusiastic participation from the students.